Optimizing Dispersion, Exfoliation, Synthesis, and Device Fabrication of Inorganic Nanomaterials Using Hansen Solubility Parameters. Issue 9 (11th April 2019) - Qin, Jinwen; Wang, Xin; Jiang, Qiwang; Cao, Minhua
Abstract: Hansen solubility parameters (HSPs) were established by Hansen in 1967 and predict miscibility between different material systems. So far, HSP theory works across polymers, crystalline bulk solids and nanomaterials and can be used to identify single solvents or, more likely, blends of solvents that deliver not only the initial solubility but also control it during reaction processes. This minireview summarizes the recent progress on HSP theory to optimize dispersion, exfoliation, synthesis, and device fabrication of inorganic nanomaterials. First, we briefly introduce HSP theory and determination of HSPs. Then, we discuss in detail the utilization of HSPs for inorganic nanomaterials, focusing on carbon nanomaterials, two‐dimensional non‐graphene nanomaterials, and metal oxide nanoparticles. Finally, challenges and perspectives of HSP theory in inorganic nanomaterials are reviewed. Abstract : Hansen solubility parameters : we summarize recent progress on using Hansen solubility parameters (HSPs) to optimize dispersion, exfoliation, synthesis, and device fabrication of inorganic nanomaterials. We briefly introduce HSPs, outline how they are determined, and discuss typical examples in inorganic nanomaterials. Challenges and perspectives for HSP theory in inorganic nanomaterials are finally presented.